Gardens of Renaissance Europe and the Islamic Empires Encounters and Confluences - Castel-Branco, Cristina; Gharipour, Mohammad; Gharipour, Mohammad; Henderson, Paula; Kaiser, Simone M.; Koch, Ebba; Pastore, Christopher; Paya, Laurent; Ruggles, D. Fairchild; Sinclair, Jill; Tchikine, Anatole (Penn State University Press, 2021)
The cross-cultural exchange of ideas that flourished in the Mediterranean during the sixteenth and seventeenth centuries profoundly affected European and Islamic society. Gardens of Renaissance Europe and the Islamic Empires considers the role and place of gardens and landscapes in the broader context of the information sharing that took place among Europeans and Islamic empires in Turkey, Persia, and India.In illustrating commonalities in the design, development, and people's perceptions of gardens and nature in both regions, this volume substantiates important parallels in the revolutionary advancements in landscape architecture that took place during the era. The contributors explain how the exchange of gardeners as well as horticultural and irrigation techniques influenced design traditions in the two cultures; examine concurrent shifts in garden and urban landscape design, such as the move toward more public functionality; and explore the mutually influential effects of politics, economics, and culture on composed outdoor space. In doing so, they shed light on the complexity of cultures and politics during the Renaissance.A thoughtfully composed look at the effects of cross-cultural exchange on garden design during a pivotal time in world history, this thought-provoking book points to new areas in inquiry about the influences, confluences, and connections between European and Islamic garden traditions.In addition to the editor, the contributors include Cristina Castel-Branco, Paula Henderson, Simone M. Kaiser, Ebba Koch, Christopher Pastore, Laurent Paya, D. Fairchild Ruggles, Jill Sinclair, and Anatole Tchikine